Death Penalty for Trading in US Dollars: The Famous Foreign Currency Dealer Cases in Soviet Lithuania - Lastauskienė, Giedrė (Teisė, 2025)
In the Soviet Union in the 1960s, criminal cases were brought against individuals who speculated (traded with the aim of making a profit) in foreign currency and valuables. There were two criminal trials that were widely publicised in Soviet Lithuania in 1962 – the Vilnius and Kaunas foreign currency dealer cases. The proceedings were also notable in that some of the defendants were sentenced to execution by firing squad. The Vilnius and Kaunas foreign currency dealer cases were examined in accordance with the 1957–1961 Soviet Criminal Law reform.Reformed criminal laws were in force in the Soviet Union. They prohibited the imposition of stricter penalties for actions committed in previous periods. However, in the case of the Vilnius foreign currency dealers, the death penalty was imposed for acts of trading in foreign currency and valuables that the defendants had carried out before the punishment of death penalty was introduced for this crime. The execution by fusillading some of the individuals convicted in the Vilnius foreign currency dealer case may have been decided by the fact that, at the initiative of the Soviet Security, a resolution of the Presidium of the Supreme Soviet of the Soviet Union which had been adopted even before the trial was submitted to the case, listing the names of persons against whom it was permitted to retroactively apply the criminal law providing for the death penalty.The case files provide no grounds to claim that the defendants’ Jewish identity was the basis for initiating the speculation cases or for the sentences that were given. However, the defendants themselves tended to emphasise that they were Jewish in their attempts to explain the reasons for their involvement in trading in valuables and their possession of the material resources for these activities.